Isolation of Extracellular Vesicles From Microalgae: A Renewable and Scalable Bioprocess - Paterna, Angela; Rao, Estella; Adamo, Giorgia; Raccosta, Samuele; Picciotto, Sabrina; Romancino, Daniele; Noto, Rosina; Touzet, Nicolas; Bongiovanni, Antonella; Manno, Mauro (Frontiers in Bioengineering and Biotechnology, 2022)
Extracellular vesicles (EVs) play a crucial role as potent signal transducers among cells, with the potential to operate cross-species and cross-kingdom communication. Nanoalgosomes are a subtype of EVs recently identified and isolated from microalgae. Microalgae represent a natural bioresource with the capacity to produce several secondary metabolites with a broad range of biological activities and commercial applications. The present study highlights the upstream and downstream processes required for the scalable production of nanoalgosomes from cultures of the marine microalgae Tetraselmis chuii. Different technical parameters, protocols, and conditions were assessed to improve EVs isolation by tangential flow filtration (TFF), aiming to enhance sample purity and yield. The optimization of the overall bioprocess was enhanced by quality control checks operated through robust biophysical and biochemical characterizations. Further, we showed the possibility of recycling by TFF microalgae cells post-EVs isolation for multiple EV production cycles. The present results highlight the potential of nanoalgosome production as a scalable, cost-effective bioprocess suitable for diverse scientific and industrial exploitations.